Systematic Review on Cesarean Scar Pregnancy (CSP) Diagnosis, Treatment and Management - Marzec, Marcelina Teresa; Łakoma, Aleksandra; Marzec, Weronika Zofia; Choiński, Maciej; Wasiewicz-Ciach, Paulina; Kuczyński, Piotr; Marszałek, Anna; Wydra-Rojek, Aleksandra; Kutyła, Katarzyna; Mokot, Wojciech Jan (Quality in Sport, 2024)
Introduction Cesarean scar pregnancy (CSP) is a rare but increasingly recognized complication where an embryo implants on the cesarean section scar. The incidence of CSP is rising in parallel with increasing global cesarean rates, posing significant health risks such as severe bleeding and uterine rupture. Early and accurate identification using criteria like the gestational sac’s position within the scar and specific ultrasound features is crucial for preventing severe outcomes. Aim of the Study To evaluate the diagnostic criteria and various treatment strategies for CSP, assessing their effectiveness and challenges. Materials and Methods A review of the literature collected in the PubMed database was performed to gather information found under the key words cesarean scar pregnancy," “ectopic pregnancy,” "CSP treatment," "uterine artery embolization," "methotrexate," "hysteroscopy," "dilation and curettage," and "chemoembolization." Summary The review discusses various treatment strategies, including methotrexate administration, UAE, and surgical options like hysteroscopy and laparoscopy, highlighting their effectiveness and associated challenges. It emphasizes the importance of tailoring treatments to individual patient conditions, with newer methods like chemoembolization showing promise in minimizing complications. The findings underscore the need for a personalized treatment approach, considering patient-specific factors and health goals. Further research is needed to refine these strategies and improve outcomes for those affected by CSP.